Becoming You While Being Me: Exploring the Limits of Christian Love and Identity - Matthew, Iain (Warszawskie Studia Teologiczne, 2023)
Does love - can love - transform one person into the other without loss of personal identity? Taking a cue from a phrase in Aquinas’s Commentary on the Sentences, we seek in the writings of St John of the Cross an understanding of how love works in relation to the identity of lover and beloved. The article considers a specific verse in his Noche poem, and four texts from the commentary on the Spiritual Canticle. The Carmelite poet’s intution about love’s efficacy then finds confirmation in texts from Ratzinger / Benedict XVI, with his hallmark attention to personal relationship.